Optimizing Critical Illness Recovery: Perspectives and Solutions From the Caregivers of ICU Survivors. (12th May 2021) - Sevin, Carla M.; Boehm, Leanne M.; Hibbert, Elizabeth; Bastin, Anthony J.; Jackson, James C.; Meyer, Joel; Quasim, Tara; Bakhru, Rita N.; Montgomery-Yates, Ashley; Slack, Andrew; Still, Mary; Netzer, Giora; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To understand the unmet needs of caregivers of ICU survivors, how they accessed support post ICU, and the key components of beneficial ICU recovery support systems as identified from a caregiver perspective. Design: International, qualitative study. Subjects: We conducted 20 semistructured interviews with a diverse group of caregivers in the United States, the United Kingdom, and Australia, 11 of whom had interacted with an ICU recovery program. Setting: Seven hospitals in the United States, United Kingdom, and Australia. Interventions: None. Measurements and Main Results: Content analysis was used to explore prevalent themes related to unmet needs, as well as perceived strategies to improve ICU outcomes. Post-ICU care was perceived to be generally inadequate. Desired caregiver support fell into two main categories: practical support and emotional support. Successful care delivery initiatives included structured programs, such as post discharge telephone calls, home health programs, post-ICU clinics, and peer support groups, and standing information resources, such as written educational materials and online resources. Conclusions: This qualitative, multicenter, international study of caregivers of critical illness survivors identified consistently unmet needs, means by which caregivers accessed support post ICU, and several care mechanisms identified by caregivers as supporting optimal ICU recovery.